Inner Scar Umbilicus: New Horizons for Vertical Abdominoplasty - Mendes, Flavio H. [UNESP]; Viterbo, Fausto [UNESP]; Luna, Ana L. A. P. [UNESP] (Lippincott Williams & Wilkins, 2018)
Background: It is reasonable that deflated tissue in massive weight loss patients may demand not only lifting but also some extent of central body tightening, by the fleur-de-lis procedure. Although achieving nice contouring results, poor visible scars, including umbilical complications, have restricted the indications for the anterior vertical approach. The purpose of this article is to present the authors' experience with the inner scar umbilical reconstruction, reflecting overall results in vertical abdominoplasties. Methods: Massive weight loss patients who underwent fleur-de-lis abdominoplasties with the inner scar umbilicus were reviewed retrospectively. The original stalk was resected along with the surgical specimen, and two marked parallel skin flaps were kept and sutured against each other into the deep medial fascia, to reconstruct the umbilical base. Additional sutures were made to approximate fat tissue immediately under and above it, enhancing a deepening effect. Conventional upper and lower vertical closure helped to establish the tridimensional shape of the new navel. Results: One hundred ten consecutive patients were studied, and 52 (47 percent) presented small inflammatory exudate arising from the inner suture, which resolved with conservative dry dressings. No further umbilical complications such as infection, necrosis, dehiscence, widening, or stenosis were reported, and all patients showed natural and scarless new navels with nice shapes and correct position. Conclusions: The inner scar umbilicus is a simple, safe, and reproducible technique, presenting low complication rates with sustainable and natural results. High-quality navel reconstruction favors the indication of vertical abdominoplasties, especially for post-bariatric surgery body contouring. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.